Milk production responses and rumen fermentation of dairy cows supplemented with summer brassicas. (5th March 2020) - Castillo-Umaña, M.; Balocchi, O.; Pulido, R.; Sepúlveda-Varas, P.; Pacheco, D.; Muetzel, S.; Berthiaume, R.; Keim, J. P.
Abstract : Forage brassicas, such as summer turnip (ST ; Brassica rapa ) and forage rape (FR ; Brassica napus ), are used as supplementary crops during summer. However, studies with lactating dairy cows fed these forages are limited and report inconsistent productive responses. The aim of this study was to determine dry matter intake, rumen fermentation and milk production responses of dairy cows in mid-lactation supplemented with and without summer ('ST' or 'FR') brassicas. Twelve multiparous lactating dairy cows were randomly allocated to three dietary treatments in a replicated 3 × 3 Latin square design balanced for residual effects over three 21-day periods. The control diet consisted of 16.2 kg DM of grass silage, 2.25 kg DM of commercial concentrate and 2.25 kg DM solvent-extracted soybean meal. For the other two dietary treatments, 25% of the amounts of silage and concentrates were replaced with FR or ST. The inclusion of forage brassicas had no effects on milk production (24.2 kg cow/day average) and composition (average milk fat and protein 43.2 and 33.6 g/l, respectively). Dry matter intake was 0.98 kg and 1.12 kg lower for cows supplemented with FR and ST, respectively, resulting in a greater feed conversion efficiency (1.35 kg milk/kg DM for ST and FR v . 1.27 kg milk/kg DM for the control diet). Intraruminal pH was lower for cows supplemented with ST compared to the control diet; however, it did not decrease below pH 5.8 at any time of the day. After feeding, the concentrations of total short-chain fatty acids (SCFAs ) in rumen contents increased with ST supplementation compared to the control diet. Inclusion of FR in the diet increased the molar proportion of acetate (68.5 mmol/100 mmol) in total SCFA at the expense of propionate, measured 6 h after feeding of the forage. The molar proportion of butyric acid was greater with ST and FR supplementation (13.1 and 12 mmol/100 mmol, respectively) than in control cows. The estimated microbial nitrogen (N) flow was 89.1 g/day greater when supplementing FR compared to the control diet. Based on the haematological measures, the inclusion of summer brassica forages did not affect the health status of the animals. These results indicate that mid-lactation dairy cows fed brassicas are able to maintain production despite the reduced intake, probably due to improved rumen fermentation and therefore nutrient utilization.